ANALYZING MARKETING STRATEGY TO INCREASING THE NUMBER OF PATIENT VISITS IN KMU MADURA EYE CLINIC - Nanik Julianti Puji Kartika; Nur Cahyadi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
To increase the number of patient visits, of course a clinic or health service agency will design a strategy to increase the number of patient visits. The KMU Madura Eye Clinic has seen an increase in the number of patient visits in recent years. This research was conducted at the KMU Madura Eye Clinic. This research uses a descriptive qualitative method. Data collection techniques using interviews and observation. The informants in this study were the head of the KMU Madura Eye Clinic branch, the ER (Eye Representative) section and the admin section. The purpose of this study was to find out and describe what strategies were designed by the KMU Madura Eye Clinic so that there was an increase in the number of patient visits. The results of this study are that the KMU Madura Eye Clinic made several strategies to increase the number of patient visits including collaborating with BPJS, influencing WOM or (Word Of Mouth), promotion through social media and making visits to FKTP (First Level Health Facilities). Of the four strategies designed as a whole greatly affect the increase in patient visits.